Proteomic comparison of basal endosperm in maize miniature1 mutant and its wild-type Mn1 - Silva-Sanchez, Cecilia; Chen, Sixue; Zhu, Ning; Li, Qin-Bao; Chourey, Prem S. (Frontiers in Plant Science, 2013)
Developing endosperm in maize seed is a major site for biosynthesis and storage of starch and proteins, and of immense economic importance for its role in food, feed and biofuel production. The basal part of endosperm performs a major role in solute, water and nutrition acquisition from mother plant to sustain these functions. The miniature1 (mn1) mutation is a loss-of-function mutation of the Mn1-encoded cell wall invertase that is entirely expressed in the basal endosperm and is essential for many of the metabolic and signaling functions associated with metabolically released hexose sugars in developing endosperm. Here we report a comparative proteomic study between Mn1 and mn1 basal endosperm to better understand basis of pleiotropic effects on many diverse traits in the mutant. Specifically, we used iTRAQ based quantitative proteomics combined with Gene Ontology (GO) and bioinformatics to understand functional basis of the proteomic information. A total of 2518 proteins were identified from soluble and cell wall associated protein (CWAP) fractions; of these 131 proteins were observed to be differentially expressed in the two genotypes. The main functional groups of proteins that were significantly different were those involved in the carbohydrate metabolic and catabolic process, and cell homeostasis. The study constitutes the first proteomic analysis of basal endosperm cell layers in relation to endosperm growth and development in maize.